Proceedings of the International Conference on English Language Teaching (ICONELT 2017) 2018
DOI: 10.2991/iconelt-17.2018.41
|View full text |Cite
|
Sign up to set email alerts
|

Padlet as media to improve writing mastery of english department students of uniska 2015-2016

Abstract: -multimedia has been spread out and used by many students in their lives, but it rarely uses multimedia as one of medias that used in teaching learning process. The objective of this study is to know whether the use of padlet as the media that can improve the students' mastery in descriptive writing, especially the students in the third semester of english departement of uniska. The research's design used was classroom action research, consisted of two cycles. Each cycles consisted of three opportunities for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 3 publications
3
8
0
1
Order By: Relevance
“…The results obviously showed that Padlet was an effective tool for learning vocabulary within the CLT environment and learner-centered settings, which is consistent with the findings of previous studies in this topic such as Lestari and Kurniawan (2018), Algraini (2014) Saepuloh and Salsabila (2020). In addition other researchers (e.g., Awaludin & Karim, 2017;Haris et al, 2017;Toti, 2018) also described it as an effective tool with a significant role in improving students' language skills as well as contributing to their positive attitudes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results obviously showed that Padlet was an effective tool for learning vocabulary within the CLT environment and learner-centered settings, which is consistent with the findings of previous studies in this topic such as Lestari and Kurniawan (2018), Algraini (2014) Saepuloh and Salsabila (2020). In addition other researchers (e.g., Awaludin & Karim, 2017;Haris et al, 2017;Toti, 2018) also described it as an effective tool with a significant role in improving students' language skills as well as contributing to their positive attitudes.…”
Section: Discussionsupporting
confidence: 90%
“…Due to these benefits, numerous surveys of attitudes toward Padlet have found positive views of the application, and researchers found that utilizing Padlet in the sphere of education increases student interest and motivation (Awaludin & Karim, 2017;Haris, Yunus, & Badusah, 2017;Saepuloh & Salsabila, 2020;Toti, 2018). Lestari and Kurniawan (2018) conducted a study Arab World English Journal www.awej.org ISSN: 2229-9327 363 that aimed to investigate the effectiveness of Padlet with regard to improving students' mastery over writing; the researchers designed their experiment in two phases and each phase included observations of student "planning, implementing, observing, and reflecting." (p. 184).…”
Section: Using Padlet As a Teaching Toolmentioning
confidence: 99%
“…The results obviously showed that Padlet was an effective tool for learning vocabulary within the CLT environment and learner-centered settings, which is consistent with the findings of previous studies in this topic such as Lestari and Kurniawan (2018) Saepuloh and Salsabila (2020). In addition other researchers (e.g., Awaludin & Karim, 2017;Haris et al, 2017;Toti, 2018) also described it as an effective tool with a significant role in improving students' language skills as well as contributing to their positive attitudes.…”
Section: Discussionsupporting
confidence: 90%
“…Due to these benefits, numerous surveys of attitudes toward Padlet have found positive views of the application, and researchers found that utilizing Padlet in the sphere of education increases student interest and motivation (Awaludin & Karim, 2017;Haris, Yunus, & Badusah, 2017;Saepuloh & Salsabila, 2020;Toti, 2018). Lestari and Kurniawan (2018) conducted a study Arab World English Journal www.awej.org ISSN: 2229-9327 363 that aimed to investigate the effectiveness of Padlet with regard to improving students' mastery over writing; the researchers designed their experiment in two phases and each phase included observations of student "planning, implementing, observing, and reflecting." (p. 184).…”
Section: Using Padlet As a Teaching Toolmentioning
confidence: 99%
“…This provides an opportunity for lecturers and students to use Padlet as a means of learning and communication academically, in this case, as a microblogging platform. Previous research has shown that the use of Padlet can increase student grades, foster interest in learning [7], motivate students to address the subject effectively and to engage in the completion of classes [12], and improve student writing achievement [13]. In addition, students give a positive attitude towards Padlet as a medium of learning [14].…”
Section: Introductionmentioning
confidence: 99%